Comamonas kerstersii Bacteremia of Unknown Origin - Kassie Rong; Johan Delport; Fatimah AlMutawa (Case Reports in Infectious Diseases)
Comamonas kerstersii (C. kerstersii) is a Gram-negative bacillus abundant in the environment and rarely implicated in human disease. Previously considered nonpathogenic, its scarcity in literature may be partly due to the unreliability of past phenotypic tests used for its identification. In recent years, the development of matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS) has enabled fast and accurate laboratory identification of C. kerstersii. Since the first report of human infection in 2013, several others have emerged, with most cases involving peritoneal infection. Here, we present a rare case of C. kerstersii bacteremia in an 82-year-old male patient. With no clear predisposing conditions, the source of his infection is unclear. We accompany this report with a review of C. kerstersii bacteremia cases found in the literature.